The rules for the publication of Spanish nursing journals - Pedro Jorge Araujo (Fundación para el Desarrollo de la Enfermería, 2012)
Objective: To analyze the rules of publication of the Spanish nursing journals. Methods: Cross-sectional observational study, conducted in forty Spanish nursing journals, which used a questionnaire with 16 items. Results: Half of the analyzed present electronic journals and nearly 30% have followed an irregular quarterly and semiannually. 97.5% of journals have a section on the types of articles and a section with general rules, and 82.5% have a section with rules for submission of illustrations, pictures, etc. and the mechanism of selection of items. The most common style for citation and bibliography is Vancouver. More than half have a section explaining the structure of the articles, 65% have no model letter of assignment of copyright and 72.5% do not have a checklist. Conclusions: Most of the journals studied have in their rules on publication a section with the types of items that can be published to follow general rules and rules for submission illustrations, pictures, etc. On the other hand, slightly more than half of the magazines have a section with the structure to be writing an article, and a considerable percentage of them do not have a sample letter of copyright assignment and a list of checks, respectively.